Changing perspectives in Legal Education: competence-based learning and the possibilities to improve access to justice via mediation skills - Loussia P. Musse Felix; André Gomma de Azevedo (Universidad de Deusto, 2015)
As one of the major Brazilian Law Schools, the University of Brasilia School of Law is at the forefront of a competence-based dispute resolution programme to be used in legal education and within the Brazilian Court system. Changes in Legal Education around the world obviate the need to integrate theoretical and practical perspectives at all levels in the formal training of new professionals in the field of Law. The University of Brasilia School of Law has participated in Tuning Latin America since 2006 and has recently adopted a Curriculum that embraces competence-based learning as part of a major change geared to bringing social, cultural and political effectiveness into the teaching of Law. This paper outlines the challenges facing the adoption of collaborative approaches to dispute resolution in the legal arena and the meta-competences and competences it entails.